Double-Junction Cascaded GaAs-Based Broad-Area Diode Lasers with 132W Continuous Wave Output Power - Jun Wang; Shaoyang Tan; Ye Shao; Wuling Liu; Kun Tian; Yao Xiao; Zhicheng Zhang; Yudan Gou; Lihong Zhu; Bangguo Wang; Shouhuan Zhou (Photonics, 2024)
Improving the output power and efficiency of broad-area diode lasers is a prerequisite for the further development of fiber lasers, solid-state laser industries, and direct semiconductor laser applications. At present, the large amount of Joule heat generated by large drive currents and limited wall-plug efficiency presents the largest challenge for improving these lasers. In this paper, a multi-junction cascade laser with low Joule heat generation is demonstrated, showing large power and conversion efficiency. We fabricated devices with different junction numbers and compared their output power. We present double-junction lasers emitting at ~915 nm with an emitter width of 500 μm, delivering 132.5 W continuous wave output power at 70 A, which is the highest power reported so far for any single-emitter laser. The power conversion efficiencies are 66.7% and 60%, at 100 W and 132 W, respectively.